Production of continuous castings from non-ferrous metals waste. - E. I. Marukovich; A. A. Andrushevich; M. N. Churik (Литьë и металлургия, 2000)
Are given the results and is shown the perspective of production of high quality billets from non-ferrous Al-Cu base metals waste by the continuous casting process.